Study of the chemical kinetics for obtaining biogas from organic wastes (non-citrus fruit residues and cattle manure) for the validation of the design and operation of an anaerobic didactic biodigester - Bonilla Bermeo, Stefanie Michelle; Chica Mero, Adrián Alexander; Vaca Chonillo, Jamilet Viviana (Ingeniería Química y Desarrollo, 2022)
This project is the assembly of three biodigesters (one with Agitation 43,10 L and two without it 3 L), the raw materials are the residues of non-citrus fruits (banana and papaya), inoculum and bovine manure previously homogenized and in different percentages of Concentration (manure-fruit ratio is 80:20). During the experimental phase, periodic measurements of control variables such as pH, chemical oxygen demand, temperature and solids content were carried out in the reactors. The rate of degradation is formulated as the generation of biogas in various conditions being hydrolysis the limiting stage of the process, we obtain an effluent rich in nitrogen and biogas with higher percentage in methane. The hydraulic residence time is of 24 days, based on the results of the experimental measurements and adjustments by the integral method by probing, it is obtained that the optimal mixture for the process is the mixture II, being a reaction of order n=1 and the kinetic constant is k=0,0781 d-1. The objective of the thesis project includes the study of the rate of degradation of non-citrus fruit residues and bovine manure with respect to a series of parameters mentioned above.
Keywords: Biodigestor; degradation; biogas; reaction kinetics; chemical oxygen demand